2014 11th International Symposium on Electronics and Telecommunications (ISETC) 2014
DOI: 10.1109/isetc.2014.7010736
|View full text |Cite
|
Sign up to set email alerts
|

Optimized process design flow for fabrication of superjunction VDMOS for enhanced R<inf>DSon</inf>A

Abstract: In this paper, we proposed a simple and optimized process design flow for the fabrication of Silicon Charge Balance (CB) Super Junction (SJ) Vertical Double Diffused MOS (VD-MOS). Deep Reactive Ion etching (DRI) is used for forming trench p-pillar with process simulation, which reduces the design complexity and number of steps required for device fabrication. The trench p-pillar that has been formed at 1100 • C using DRI causes crystal defects. We remove these defects by annealing at 1150 • C which results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…As we have observed that the SJ-I and SJ devices have bidirectional electric field. To achieve premature BV both electric fields resultant should be equal to E c [14]. Using the above analysis, we have predicted that the proposed SJ-I device achieved higher BV than conventional SJ devices as shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…As we have observed that the SJ-I and SJ devices have bidirectional electric field. To achieve premature BV both electric fields resultant should be equal to E c [14]. Using the above analysis, we have predicted that the proposed SJ-I device achieved higher BV than conventional SJ devices as shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Here, the observation shows that the higher drive current flow in the s-SJ device as compared to the SJ device for all considered bias conditions due to strain effect. We have developed simple method for the calculation of R on A [7]. In this method, the R on A of the device is the ratio of applied V DS to the resulting J D in the linear region of operation and it is variable with the applied V GS .…”
Section: Resultsmentioning
confidence: 99%
“…At the top gate oxide thickness of 100 nm is grown by wet oxidation at 900 • C for 125 minutes. Here the gate is formed using poly-Si and S/D ohmic contacts are formed using aluminum metallization [7]. The proposed device unit cell dimension is 5 × 40 µm 2 and the channel length is 1.4 µm.…”
Section: Stepmentioning
confidence: 99%
See 2 more Smart Citations